2006
DOI: 10.1080/08977190601075865
|View full text |Cite
|
Sign up to set email alerts
|

Potential involvement of BMP receptor type IB activation in a synergistic effect of chondrogenic promotion between rhTGFβ3 and rhGDF5 or rhBMP7 in human mesenchymal stem cells

Abstract: Chondrogenic promotion by rhGDF5 with or without rhTGFbeta3 was studied in pellet culture of human mesenchymal stem cells (HMSCs). A synergy between rhGDF5 and rhTGFbeta3 was observed in promoting chondrogenesis. rhBMP2, rhBMP6, rhBMP7 and rhTGFbeta1 were further tested and showed the same effect. To explore the mechanism, the expression of TGFbetatype I and II receptors, ALK5, ALK2, ALK3, ALK6, TGFbetaRII, BMPRII, ActRII was studied. ALK6 showed increase by the rhTGFbeta1 or rhTGFbeta3 treatment. ALK6 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…The mechanism of BMP-7 enhancement for TGF-b3-mediated chondrogenic differentiation is not clear. It has been reported that the TGF-b type III receptor functions as a BMP cell surface receptor which binds to multiple members of the BMP subfamily including BMP-7 [Kirkbride et al, 2008], and TGFb3 mediates the upregulation of the type I BMP receptor, ALK6 [Xu et al, 2006] through which BMP-7 and other BMPs are known to signal [Yamashita et al, 1996]. Taken together, the recent advance suggests that mutual regulation or receptor activation may amplify and enhance the effects of TGF-b and BMPs.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The mechanism of BMP-7 enhancement for TGF-b3-mediated chondrogenic differentiation is not clear. It has been reported that the TGF-b type III receptor functions as a BMP cell surface receptor which binds to multiple members of the BMP subfamily including BMP-7 [Kirkbride et al, 2008], and TGFb3 mediates the upregulation of the type I BMP receptor, ALK6 [Xu et al, 2006] through which BMP-7 and other BMPs are known to signal [Yamashita et al, 1996]. Taken together, the recent advance suggests that mutual regulation or receptor activation may amplify and enhance the effects of TGF-b and BMPs.…”
Section: Discussionmentioning
confidence: 90%
“…Chondrogenic differentiation of BM MSCs can generally be induced by stimulation with all isoforms of TGF-b in serum-free medium at high cell density [Mackay et al, 1998;Pittenger et al, 1999]. However, previous reports have suggested that TGF-b alone may not be sufficient for chondrogenic induction, and that a combination of growth factors is necessary [Sekiya et al, 2001;Xu et al, 2006;Shen et al, 2008]. We present here that BMP-7, when supplemented in chondrogenic differentiation medium containing TGF-b3, enhanced the mRNA and/or protein expression of chondrogenic markers COL2A1, COL9A1, COL10A1, and SOX9, and increased extracellular matrix proteoglycan deposition.…”
Section: Discussionmentioning
confidence: 98%
“…BMP-2, and -7 have been shown to be the more chondrogenic of the BMPs in MSCs in vitro (Majumdar et al, 2001;Sekiya et al, 2005;Fan et al, 2010), and both have shown promising results in animal models (Badlani et al, 2009;Blaney Davidson et al, 2007b). The chondrogenic effect of BMP-7 is synergistically increased when used in combination with TGF-β (Xu et al, 2006;Kim and Im, 2009) or insulin-like growth factor (IGF)-1 (Loeser et al, 2003;Chubinskaya et al, 2007a). BMP-2 is also a strong inducer of osetogenesis and is used clinically for bone fusion (Tang et al, 2011;Hamilton et al, 2011), which needs to be taken into consideration if using BMP-2 for cartilage generation.…”
Section: Growth Factors 411 Transforming Growth Factor-β Superfamilymentioning
confidence: 99%
“…BMP-2, and -7 have been shown to be the more chondrogenic of the BMPs in MSCs in vitro (Majumdar et al, 2001;Sekiya et al, 2005;Fan et al, 2010), and both have shown promising results in animal models (Badlani et al, 2009;Blaney Davidson et al, 2007b). The chondrogenic effect of BMP-7 is synergistically increased when used in combination with TGF-β (Xu et al, 2006;Kim and Im, 2009) or insulin-like growth factor (IGF)-1 (Loeser et al, 2003;Chubinskaya et al, 2007a). BMP-2 is also a strong inducer of osetogenesis and is used clinically for bone fusion (Tang et al, 2011;Hamilton et al, 2011), which needs to be taken into consideration if using BMP-2 for cartilage generation.…”
Section: Growth Factors 411 Transforming Growth Factor-β Superfamilymentioning
confidence: 99%